Cnidoscolus blistering yellow mosaic virus: a new begomovirus isolated from Cnidoscolus urens in Brazil - Costa de Oliveira, Maria Helloá; Ferro, Mayra; Monteiro Feijó, Frederico; Silvestre de Andrade Lima, Gaus; Pereira Assunção, Iraildes; Cavalcanti da Silva, Sarah Jacqueline (Comunicata Scientiae, 2021)
Members of the genus Begomovirus have circular single-strand DNA genome encapsidated into quasi-icosahedral particles, which are transmitted by the Bemisia tabaci complex, with non-cultivated hosts acting as reservoirs for these viruses. In this study a new begomovirus infecting Cnidoscolus urens (Euphorbiaceae) from Brazil has been characterized. The complete DNA-A sequence was used for species demarcation, phylogenetic and recombination analyzes with other previously reported begomoviruses. The DNA-A (2585 nt) has a genome organization that is typical of the New World bipartite begomovirus, most closely related to tomato yellow spot virus, with 80.6% nucleotide identity. Based on the identity criterion for DNA-A established by the Geminiviridae Study Group of the International Committee on Taxonomy of Viruses of ≥ 91%, this isolate should be considered a member of a new species, for which the name “Cnidoscolus blistering yellow mosaic virus” (CnBYMV) is proposed. Phylogenetic analysis revealed that CnBYMV grouped with begomoviruses described in cultivated and non-cultivated plants from Brazil. Results of recombination analysis indicated that the novel begomovirus was a recombinant, with cnidoscolus mosaic leaf deformation virus and sida mottle virus as probable parents.